2460: Change in duration of postoperative antibiotic prophylaxis in esophagectomy patients: Outcomes in a single academic institution - Wang, Sue (J Clin Transl Sci, 2018)
OBJECTIVES/SPECIFIC AIMS: Ivor-Lewis esophagectomy (ILE) is an invasive surgical procedure with a high incidence of postoperative pneumonia. Antibiotic prophylaxis could reduce respiratory infections but increase Clostridium difficile and antibiotic resistance. Our institution reduced the duration of piperacillin-tazobactam prophylaxis following ILE from 4 to 1 day or less in January 2015. We evaluated short-term outcomes in ILE patients before and after this institutional change. METHODS/STUDY POPULATION: Retrospective cohort study of all ILE patients from 2012 to 2016. We confirmed antibiotic duration directly from nursing medication administration records. The primary outcomes of this study were rates of C. difficile and postoperative pneumonia. Secondary outcomes include other infection, length of hospital stay, and readmission within 30 days. We used logistic regression to analyze impact of days of antibiotics and χ(2) or Fischer exact tests for categorical variables. RESULTS/ANTICIPATED RESULTS: Of 104 ILE patients, 40.4% (n=42) were after January 2015, 11.5% developed pneumonia and 5.8% developed C. difficile colitis. ILE patients received more days of antibiotics before the institutional change compared with after (6.1 vs. 2.9 d, p<0.01). For a 1-day increase in antibiotic duration, the odds of acquiring C. difficile increased significantly by 1.2 (p=0.03). Before compared with after the institutional change, rates of C. difficile were 8.1% Versus 2.4% (p>0.2), rates of pneumonia were 11.3% Versus 11.9% (p>0.2), and length of stay was 10.9 Versus 10.5 days (p>0.2), respectively. DISCUSSION/SIGNIFICANCE OF IMPACT: Institutional policy can have an impact on patient outcomes. Antibiotic stewardship is associated with reduced rates of inpatient C. difficile. Our study suggests reduced antibiotics are not associated with pneumonia, although larger studies are necessary to confirm this finding. Surgeons should consider the benefit of decreased rates of C. difficile before administering prolonged antibiotic prophylaxis following esophagectomies.